Pengaruh Penerapan Model Pembelajaran Creative Problem Solving (CPS) Terhadap Hasil Belajar Siswa Mas Terpadu Guguak Randah Pada Ekstrakulikuler TIK - Rabiatul Mauida; Supratman Zakir; Wedra Aprison; Liza Efriyanti (Politeknik Negeri FakFak, 2024)
This study aims to improve extracurricular learning outcomes in class X of Guguak Randah integrated MAS by applying a creative problem-solving learning model. Through interviews with the integrated teacher, Mrs. Syarifah,, it was revealed that the learning process still relies on the lecture method and teacher-centered approach which causes a lack of student interest in learning. To overcome this problem, the researcher is interested in applying a creative problem-solving learning model so that students are more involved and their learning outcomes improve. The research used a quasi-experimental method with a post-test only control group design. In this context, the use of the Creative Problem Solving model on students of class X IPA integrated MAS Guguak Randah showed a significant effect on learning outcomes. The t-test results confirmed a significant difference between the experimental group that applied the creative learning model and the control group. Thus, the application of this model can stimulate student creativity, improve learning interest, and make the learning process more interesting and interactive.